Multiple Endocrine Neoplasia Type 1 (MEN1): An Update and the Significance of Early Genetic and Clinical Diagnosis - Kamilaris, Crystal D. C.; Stratakis, Constantine A. (Frontiers in Endocrinology, 2019)
Multiple endocrine neoplasia type 1 (MEN1) is a rare hereditary tumor syndrome inherited in an autosomal dominant manner and characterized by a predisposition to a multitude of endocrine neoplasms primarily of parathyroid, enteropancreatic, and anterior pituitary origin, as well as nonendocrine neoplasms. Other endocrine tumors in MEN1 include foregut carcinoid tumors, adrenocortical tumors, and rarely pheochromocytoma. Nonendocrine manifestations include meningiomas and ependymomas, lipomas, angiofibromas, collagenomas, and leiomyomas. MEN1 is caused by inactivating mutations of the tumor suppressor gene MEN1 which encodes the protein menin. This syndrome can affect all age groups, with 17% of patients developing MEN1-associated tumors before 21 years of age. Despite advances in the diagnosis and treatment of MEN1-associated tumors, patients with MEN1 continue to have decreased life expectancy primarily due to malignant neuroendocrine tumors. The most recent clinical practice guidelines for MEN1, published in 2012, highlight the need for early genetic and clinical diagnosis of MEN1 and recommend an intensive surveillance approach for both patients with this syndrome and asymptomatic carriers starting at the age of 5 years with the goal of timely detection and management of MEN1-associated neoplasms and ultimately decreased disease-specific morbidity and mortality. Unfortunately, there is no clear genotype-phenotype correlation and individual mutation-dependent surveillance is not possible currently.